Left-Right Spectrum and Democratic Backsliding: India, Indonesia, and the Philippines in Comparative Perspectives - Faishal Aminuddin (Pusat Riset Politik BRIN, 2023)
The phenomena of democratic backsliding in Asia requires an in-depth analysis of social factors that contribute to the decline of democracy. This study will explore the intersections between a country’s Left-Right (L-R) political spectrum, their state of political parties, and the rise of populist leaders. How far do these three political phenomena contribute to the occurrence of democratic backsliding? By comparing findings from India, Indonesia, and the Philippines, this study aims to explain how the L-R political spectrum of voters is related to their party preferences. The study finds this variable to be strongly related to the emergence of strong leaders who utilize identity politics and political ideology as an adhesive tool for gathering mass public support. These populist tactics, in turn, chisel away mechanisms and claims for democratic accountability.